2019
DOI: 10.4103/jets.jets_80_18
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cervical collar immobilization on optic nerve sheath diameter

Abstract: Background: Prior research has revealed that cervical collars elevate intracranial pressure (ICP) in patients with traumatic brain injury. Two recent small studies evaluated the change in optic sheath nerve diameter (ONSD) measured by ultrasound as a proxy for ICP following cervical collar placement in healthy volunteers. Objective: We sought to validate the finding that ONSD measured by ultrasound increases after cervical collar placement within an independent data set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The mean ONSD in the axial plane for the right and left optic nerves was 5.04 ± 0.46 mm and 5.11 ± 0.46 mm respectively on CT images without cervical collar patients. These findings suggest that patients without cervical collars and without orbital or cranial pathology have similar mean ONSD measurements to those made in healthy patients on CT. Yard et al [10] evaluated whether the cervical collar change the ONSDs, and it was observed that the cervical collar increased the ONSD. Colak et al [16] evaluated the relationship between the ONSD and cervical collar use in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean ONSD in the axial plane for the right and left optic nerves was 5.04 ± 0.46 mm and 5.11 ± 0.46 mm respectively on CT images without cervical collar patients. These findings suggest that patients without cervical collars and without orbital or cranial pathology have similar mean ONSD measurements to those made in healthy patients on CT. Yard et al [10] evaluated whether the cervical collar change the ONSDs, and it was observed that the cervical collar increased the ONSD. Colak et al [16] evaluated the relationship between the ONSD and cervical collar use in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, the optic nerve sheath diameter (ONSD) has been shown to be a useful marker for indirectly measuring the ICP. [8][9][10] ONSD can be measured with computed tomography (CT), magnetic resonance imaging (MRI), or ultrasound (US). [11,12] In the literature, there are many studies in which ONSD measurements of trauma patients with cervical collars were obtained using the US.…”
Section: Introductionmentioning
confidence: 99%
“…When performing serial exams, be careful to use the same positioning and environment, or account for changes in positioning or other activities that increase ICP such as coughing, cervical collar, and derangements such as kinked endotracheal tube [78].…”
Section: Neurological Point Of Care Ultrasoundmentioning
confidence: 99%
“…10,11 Recent evidence suggests the application of a rigid cervical collar for a short period results in a change of optic nerve sheath diameter in healthy volunteers. 12 So the ideal C-spine clearance protocols must balance the risk of missed injury against the potential for increased morbidity from prolonged spinal immobilisation.…”
Section: Introductionmentioning
confidence: 99%